Pelatihan Memahami Hadits “Hidupkanlah Saya Miskin” dengan Metode Semantik di Pesantren Modern Nurul Huda-Cikarageman-Setu-Bekasi - Khairil Ihsan Siregar (Satwika: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to meet the needs of partners in understanding the hadith of the Prophet Muhammad SAW. This community service activity was carried out at the Nurul Huda Modern Islamic Boarding School, Cikaregenan Setu-Bekas. The training was carried out with the theme "Training to Understand the Hadith "Live Me the Poor" with the semantic method". This theme was brought up based on the suitability of the field of knowledge of the Islamic Religious Education Study Program lecturer at FIS UNJ in the concentration of hadith studies and the need to understand hadith by partners. Through this training, the understanding of the hadith of the Prophet SAW This training uses a semantic approach that provides increased understanding for teachers at this Islamic boarding school. The result is an increase in the understanding of teachers through training to recognize hadith texts and then elaborate on the approach of semantic theories to each word's meaning in the hadith or overall sentence structure. Then, to strengthen the theme of the meaning of the hadith that is the sample in this training, it is converted (I'tibar) with the meaning of other hadiths so that the meaning of the hadith that is an example is still valid because it does not contradict the Koran and other hadiths. This program recommends that the understanding of hadis require the comprehensive understanding of the Quran and hadith as well as understanding the context of the hadith. ABSTRAK Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memenuhi kebutuhan mitra dalam memahami hadist Nabi Muhammad SAW. Pada kegiatan pengabdian kepada masyarakat kali ini dilaksanakan di Pesantren Modern Nurul Huda Cikaregenan Setu-BekasI. Pelatihan yang dilaksanakan bertema “Pelatihan Memahami Hadits “Hidupkanlah Saya Miskin‟ dengan metode semantik”. Tema ini diusung berdasarkan kesesuaian bidang ilmu dosen Prodi Pendidikan Agama Islam FIS UNJ dalam konsentrasi kajian hadits dan kebutuhan memahami hadits oleh mitra. Melalui pelatihan ini maka pemahaman mengenai hadits Nabi Saw. Pelatihan ini menggunakan pendekatan semantik yang memberikan peningkatan pemahaman bagi guru-guru di Pesantren ini. Hasilnya yaitu bertambahnya pemahaman guru-guru melalui pelatihan mengenal teks-teks hadits kemudian dielaborasikan dengan pendekatan teori-teori semantik pada setiap makna kata dalam hadits atau struktur kalimat secara keseluruhan. Lalu untuk menguatkan tema makna hadits yang menjadi sample dalam pelatihan ini dikonversikan (I’tibar) dengan makna hadits-hadits lain sehingga makna hadits yang menjadi contoh masih valid karena tidak berlawanan dengan al-Qur’an dan hadits lainnya. Rekomendasi dari kegiatan pengabdian ini adalah hendaknya hadis dipahami secara komprehensif dengan melibatkan naskh dari Al-Quran dan Al-Hadis serta memperhatikan konteks hadis terjadi.